Integrasi Model ASSURE dan Metode Think Pair Square dalam Meningkatkan Hasil Belajar Matematika - Utami, Desi Tri; Purbasari, Dita Anggi (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aims to examine the effectiveness of integrating the ASSURE model with the Think Pair Square (TPSq) cooperative learning method in improving students’ mathematics learning outcomes, particularly on the topics of matrices and determinants. The research employed a Classroom Action Research approach conducted in three cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 25 students of the Mechanical Engineering Study Program at Politeknik Pratama Mulia Surakarta. Data were collected through observation, learning achievement tests, documentation, and interviews, and were analyzed using descriptive quantitative and qualitative techniques. The results showed a significant improvement in students’ learning outcomes and engagement across all cycles. The average student score increased from 64.72 in the pre-cycle to 83.48 in cycle III, while the learning mastery rate rose from 44% to 88%. The average activity score also improved from 2.6 (fairly active) to 3.8 (highly active). The integration of the ASSURE model and TPSq method created a more interactive, collaborative, and student-centered learning process, which positively impacted students’ learning activities and mathematics achievement.